Regional co-operation and protection of the marine environment under international law : the Black Sea - Oral, Nilufer (Legal aspects of sustainable development, 2013)
In Regional Co-operation and Protection of the Marine Environment under International Law: The Black Sea, Nilufer Oral examines the regional co-operation mechanism for protection and preservation of the Black Sea marine environment within the framework of international law, and subsequently identifies the necessary components for a robust regional regime based on best legal practices.